Вплив цифрової економіки на інституційне середовище - Єременко, Денис Володимирович; Єременко, Лариса В’ячеславівна; Yeremenko, Denys; Yeremenko, Larysa (Запоріжжя : ТДАТУ, 2024)
UA: Стаття аналізує вплив цифрових технологій, таких як штучний інтелект, цифрові платформи, блокчейн, Інтернет речей, на інституційне середовище. Розглянуто позитивні ефекти та загрози цифровізації економіки. Цифрові технології зменшують трансакційні витрати, руйнуючи існуючі пастки. Інституції тиснуться цифровими технологіями, змінюються або зникають, утворюючи інституційний вакуум. Вплив цифрових технологій на інституційне середовище може бути прямим та опосередкованим, включаючи цифровізацію інститутів, підвищення ефективності, руйнування старих пасток та виникнення нових. Для коригування та створення нових інститутів пропонується застосовувати принципи інституційного проєктування. EN: The article analyzes the qualitative change in the institutional environment under the influence of the spread of new digital technologies such as artificial intelligence, digital platforms, blockchain, and the Internet of Things. The positive effects, as well as threats and risks of digitalization of the economy are identified. It has been revealed that digital technologies significantly reduce transaction costs and thereby destroy existing institutional traps. Extrapolation of this trend into the future has shown that we are not in danger of the "death of institutions", but at the same time, the effect of Coase’s theorem should fully manifest itself. However, existing institutions are under pressure from digital technologies, are being transformed or are dying out. At the same time, areas of institutional vacuum arise when new digital technologies remain insufficiently institutionalized for quite a long time, and their capabilities are not fully used. The influence of new digital technologies on the economy and on the institutional environment, as well as the consequences of such influence, has been determined. It is shown that the impact of digital technologies on the institutional environment can be direct and indirect. At the same time, the essence of the qualitative changes taking place in the institutional environment under the influence of digitalization can be summarized in the following ways: digitalization of the institutions themselves, increasing the effectiveness of existing institutions, the destruction of existing institutional traps and the emergence of new ones, the emergence of an institutional vacuum, the destruction and decrease in the effectiveness of existing institutions. To adjust the existing and develop new institutions of the digital economy, it is proposed to use the principles of institutional design.
The impact of the digital economy on the institutional environment
Keywords: інституційне середовище; цифровізація економіки; штучний інтелект; цифрова платформа; трансакційні витрати; інституційні пастки; інституційний вакуум; institutional environment; digitalization of the economy; artificial intelligence; digital platform; transaction costs; institutional traps; institutional vacuum